The impact of board characteristics on executive compensation: evidence from Jakarta Islamic Index Company - Ishak, Khodijah; Zarefar, Arumega (Jurnal Siasat Bisnis, 2024)
Purpose – This study aims to examine the effect of board characteristics on CEO compensation. The board characteristics examined in this study include board independence and gender diversity consisting of woman on board and independent woman board on CEO compensation.Design/methodology/approach – The population in this study is a company belonging to the Jakara Islamic Index (JII) at the Indonesian Stock Exchange for the period 2012 - 2016. The sample in this research was determined by purposive sampling method with a total sample of 75 annual reports.Findings – The results show that independent board gender diversity consisting of female boards and independent female boards has no effect on CEO compensation.Research limitations/implications – The sample of this study is a company with shares included in the Jakarta Islamic Index on the Indonesian Stock Exchange (IDX) with an observation period of 2012-2016. Hypothesis testing in this study using multiple linear regression analysis.Practical implications – Boards to oversee and control the actions of opportunists manager, and define the most important decisions of companies, one of which compensation for the CEO, so that corporate objectives can be achieved. With the larger board size will increase oversight function of the board to act opportunistically manager so control oversight of CEO compensation more stringent design and can be defined more precisely.Originality/value – Research on the role of women in board composition is gaining attention, but not much has been explored in a country with a strong patriarchal culture like Indonesia.